2004
DOI: 10.1007/s00424-004-1356-4
|View full text |Cite
|
Sign up to set email alerts
|

Increase in intracellular Cl? concentration by cAMP- and Ca2+-dependent stimulation of M1 collecting duct cells

Abstract: In the lungs of cystic fibrosis (CF) patients, mutations of the cystic fibrosis transmembrane conductance regulator (CFTR) lead to defective Cl- secretion and hyperabsorption of electrolytes. This may be a an important cause for the defective mucociliary clearance in CF lungs. Previous studies have suggested that inhibition of ENaC during activation of CFTR or by purinergic stimulation could be related to an increase in the intracellular [Cl-]i. This was examined in the present study using cultured mouse M1 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…TMEM16 Proteins Are Essential for RVD in HEK293 CellsTo further confirm the role of TMEM16 channels for I Cl,swell and RVD we loaded HEK293 cells with the fluorescence dye calcein (28). Hypotonic bath solution induced cell swelling and decreased calcein fluorescence, which was followed by a 98% recovery after 20 min, indicating RVD (Fig.…”
Section: Volume 284 • Number 42 • October 16 2009mentioning
confidence: 85%
“…TMEM16 Proteins Are Essential for RVD in HEK293 CellsTo further confirm the role of TMEM16 channels for I Cl,swell and RVD we loaded HEK293 cells with the fluorescence dye calcein (28). Hypotonic bath solution induced cell swelling and decreased calcein fluorescence, which was followed by a 98% recovery after 20 min, indicating RVD (Fig.…”
Section: Volume 284 • Number 42 • October 16 2009mentioning
confidence: 85%
“…The authors suggest its use for the treatment of fluid loss in acute watery diarrhea. SP-303 is the active agent of Provir, a C. lechleri derived product with antisecretory properties 206,207 and hence useful to control fluid loss and diarrhea. SP-303 has been indicated particularly for patients of AIDS, common victims of diarrhea.…”
Section: Antispasmodic and Anti-diarrheicmentioning
confidence: 99%
“…Evidence has emerged from recent studies that, indeed, intracellular Cl − concentration ([Cl − ] i )p lays an important role in the regulation of the activity of ENaC in epithelia. 71 The effect of [Cl − ] i on ENaC was first described in our studies in isolated mouse mandibular duct cells. 72,73 Subsequent studies reported a similar negative relationship between Cl − transport 74,75 71 Thus the change in [Cl − ] i during P2Y 2 R stimulation, which is associated with activity of the basoalteral Na + /K + /2Cl − co-transporter,may at least in part, play a role in the inhibitory effect of nucleotides on ENaC.…”
Section: G-protein βγ Subunits Play a Role In The P2y 2 R Inhibition mentioning
confidence: 99%
“…71 The effect of [Cl − ] i on ENaC was first described in our studies in isolated mouse mandibular duct cells. 72,73 Subsequent studies reported a similar negative relationship between Cl − transport 74,75 71 Thus the change in [Cl − ] i during P2Y 2 R stimulation, which is associated with activity of the basoalteral Na + /K + /2Cl − co-transporter,may at least in part, play a role in the inhibitory effect of nucleotides on ENaC. Since bumetanide inhibits only the effect of apical UTP on the activity of ENaC in FRTcells ( Figure 4B), it is tempting to speculate that intracellular Cl − might be an important component of the PTX-insensitive P2Y 2 Rs ignalling pathway that is exclusive tot he receptor in the apical membrane.…”
Section: G-protein βγ Subunits Play a Role In The P2y 2 R Inhibition mentioning
confidence: 99%